(untitled) (Лучшие интеллектуальные исследования, 2025)
The integration of technology in education has revolutionized the way subjects are taught and learned, and Medical English is no exception. English for Medical Purposes (EMP), as defined by John Maher (1986), refers to the specialized teaching of English to healthcare professionals, including doctors, nurses, and other medical personnel, to enhance their communication skills in a medical context. With the increasing globalization of healthcare, the ability to communicate effectively in English has become a critical skill for medical professionals. This paper explores the ways in which technology can be integrated into the teaching of Medical English, the benefits it offers, and the tools that can be utilized to enhance learning outcomes.